REPRESENTATION OF JAPANESE CULTURE IN THE FILM NIHONJIN NO SHIRANAI NIHONGO (A SEMIOTIC STUDY) - MILENIA SEVTIANI; Izmayanti, Dewi Kania; Irma; Amril, Oslan (Program Studi Sastra Jepang Fakultas Ilmu Budaya Universitas Bung Hatta, 2024)
Abstract Japan has succeeded in maintaining its culture from traditional to modern culture. Thanks to its success, Japan has been highly regarded by other countries. The large number of enthusiasts outside Japan who watch anime films proves that Japanese culture is not only popular in Japan but also outside Japan. One example is the film